2008
DOI: 10.1590/s1517-83822008000100013
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of campylobacter species in healthy well-nourished and malnourished children

Abstract: The occurrence of Campylobacter species in healthy, well-nourished and healthy, malnourished children of low socioeconomic level in Southern Chile was determined. Campylobacter carriers were significantly most frequent among malnourished (31.4%) than among well-nourished (9.9%) children. Six species were isolated from malnourished children whereas four were found among well-nourished children. C. upsaliensis was the most frequent (13.3%) species isolated from malnourished children, followed by C. lari (7.6%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 15 publications
1
15
0
2
Order By: Relevance
“…Similarly, Fernandez et al (2008) found that malnourished children in Chile were more frequent carriers of Campylobacter spp. (31.4%) than well-nourished children (9.9%).…”
Section: Malnutritionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Fernandez et al (2008) found that malnourished children in Chile were more frequent carriers of Campylobacter spp. (31.4%) than well-nourished children (9.9%).…”
Section: Malnutritionmentioning
confidence: 88%
“…The genus Campylobacter is comprised of an estimated 14 to 20 species (Debruyne, 2005;Fernandez, 2008) and of these species Campylobacter jejuni and Campylobacter coli are most frequently associated with cases of campylobacteriosis.…”
Section: Genus and Species Descriptionmentioning
confidence: 99%
“…2 Campylobacter jejuni and Campylobacter coli are the genuses which cause disease symptoms most frequently. 3 Progress in molecular techniques and the development of innovative culture methods has led to the isolation of other genuses than Campylobacter jejuni/coli such as C. concisus, C. upsaliensis and C. ureolyticus. 4 The Campylobacter genus is comprised of 20 species and subspecies.…”
mentioning
confidence: 99%
“…4 The Campylobacter genus is comprised of 20 species and subspecies. 3 The clinical manifestations of Campylobacter infections are caused not only by gastrointestinal infection but also by periodontitis and inflammatory bowel disease. In some situations, a life-threatening generalized infection of the whole human body may be a complication of intestinal infection.…”
mentioning
confidence: 99%
“…Após várias alterações na estrutura taxonômica do gênero (GALATE, BANGDE, 2013), em 1963, Sebald e Véron, nomearam o gênero como Campylobacter (BUTZLER et al, 1973;GALATE e BANGDE, 2013). A nomenclatura foi baseada no formato espiral do micro-organismo: Campylobacter origina-se da palavra grega campylos (curvos) e bacter (bactéria) (GARCÍA e CRAVIOTO, 2007;FERNÁNDEZ, 2008;QUETZ, 2009).…”
Section: Caracterização Do Gênero Campylobacterunclassified